The intellectual culture of the English country house, 1500 - 1700 - Dimmock, Matthew 1975- (Manchester University Press, 2018)
The intellectual culture of the English country house is a ground-breaking collection of essays by leading and emerging scholars, which uncovers the vibrant intellectual life of early modern provincial England. The essays in the volume explore architectural planning; libraries and book collecting; landscape gardening; interior design; the history of science and scientific experimentation; and the collection of portraits and paintings. The essays demonstrate the significance of the English country house (e.g. Knole House, Castle Howard, Penshurst Place) and its place within larger local cultures that it helped to create and shape. They provide a substantial overview of the country house culture of early modern England and the complicated relationship between the provinces and the national, the country and the city, in a period of rapid social, intellectual and economic transformation. It will appeal to anyone interested in the culture of the country house and its place in early modern England